Respuesta :
x^2 + y^2 - 2x + 7y + 1 = 0
(x^2 - 2x) + (y^2 + 7y) + 1 = 0
(x^2 - 2x + 1) + (y^2 + 7y) + 1 = 0+1
(x^2 - 2x + 1) + (y^2 + 7y + 49/4) + 1 = 0+1+49/4
(x - 1)^2 + (y + 7/2)^2 + 1 = 0+1+49/4
(x - 1)^2 + (y + 7/2)^2 + 1-1 = 0+1+49/4-1
(x - 1)^2 + (y + 7/2)^2 = 49/4
(x - 1)^2 + (y + 7/2)^2 = (7/2)^2
The final answer is choice B
(x^2 - 2x) + (y^2 + 7y) + 1 = 0
(x^2 - 2x + 1) + (y^2 + 7y) + 1 = 0+1
(x^2 - 2x + 1) + (y^2 + 7y + 49/4) + 1 = 0+1+49/4
(x - 1)^2 + (y + 7/2)^2 + 1 = 0+1+49/4
(x - 1)^2 + (y + 7/2)^2 + 1-1 = 0+1+49/4-1
(x - 1)^2 + (y + 7/2)^2 = 49/4
(x - 1)^2 + (y + 7/2)^2 = (7/2)^2
The final answer is choice B
Answer:
The correct option B [tex](x -1)^{2} + (y +\frac{7}{2})^{2} = (\frac{7}{2})^{2}[/tex]
Step-by-step explanation:
We need to find out the correct option which is similar to the expression;
[tex]x^{2} + y^{2}- 2x + 7y + 1 = 0[/tex]
combine the similar variable together
[tex](x^{2} - 2x) + (y^{2} + 7y) + 1 = 0[/tex]
Add 1 both the sides,
[tex](x^{2} - 2x + 1) + (y^{2} + 7y) + 1 = 0+1[/tex]
Add both the sides by [tex]\frac{49}{4}[/tex]
[tex](x^{2} - 2x + 1) + (y^{2} +\frac{49}{4}+ 7y) + 1 = 0+1 + \frac{49}{4}[/tex]
[tex](x^{2} - 2x + 1) + (y +\frac{7}{2})^{2} + 1 = 0+1 + \frac{49}{4}[/tex]
Subtract both the sides by 1,
[tex](x^{2} - 2x + 1) + (y +\frac{7}{2})^{2} + 1-1 = 0+1 + \frac{49}{4}-1[/tex]
[tex](x^{2} - 2x + 1) + (y +\frac{7}{2})^{2} = \frac{49}{4}[/tex]
[tex](x -1)^{2} + (y +\frac{7}{2})^{2} = (\frac{7}{2})^{2}[/tex]
This is equivalent to option B
Therefore the correct option B [tex](x -1)^{2} + (y +\frac{7}{2})^{2} = (\frac{7}{2})^{2}[/tex]